Global attractivity of a rational difference equation with higher order and its applications - Xianyi Li; Luyao Lv (Mathematical Modelling and Control)
We study in this paper the global attractivity for a higher order rational difference equation. As application, our results not only include and generalize many known ones, but also formulate some new results for several conjectures presented by Camouzis and Ladas, et al.